2021
DOI: 10.3390/jpm11070599
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Infection Profiles of Expectant Mothers with COVID-19 and Impacts on Maternal and Perinatal Outcomes between the First Two Waves of the Pandemic

Abstract: During 2020, Coronavirus Disease-19 (COVID-19) incidence fluctuated in two clear waves across the spring and autumn periods. This study was designed to compare the maternal and perinatal clinical outcomes in obstetrics patients with COVID-19 between the two waves of infection in Spain. We conducted an observational, analytical, ambispective cohort study with longitudinal follow-up of mothers with confirmed SARV-CoV-2 infection from different hospitals in our country between March–November 2020. We recruited 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…During this period, vaccination had not been approved for pregnant women 9 . Our findings are consistent with other studies, 10 in which more women presented in advanced pregnancy causing more maternal morbidity and mortality.…”
Section: Discussionsupporting
confidence: 89%
“…During this period, vaccination had not been approved for pregnant women 9 . Our findings are consistent with other studies, 10 in which more women presented in advanced pregnancy causing more maternal morbidity and mortality.…”
Section: Discussionsupporting
confidence: 89%
“… 9 A study performed with Spanish obstetric COVID-19 patients showed worsening respiratory symptoms during the second wave. 19 A major data analysis carried out in the UK covering the waves March 2020-November 2020 and December 2020-February 2021 showed that among hospitalized COVID-19 pregnant women aged 20-39 years, 10% received critical care, 1% died, and 18% had a preterm birth. In addition, since the B.1.1.7 variant became predominant (second wave), the number of pregnant women with COVID-19 admitted to the hospital were more than twice higher and more likely to require respiratory support, and obesity was significantly associated with adverse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…An observational analytical study on 1295 COVID-19 infected pregnant women, comparing two waves in Spain reported a strong correlation of maternal morbidity with perinatal morbidity similar to our study. On univariate analysis mechanical ventilation and maternal ICU admission showed a positive association with perinatal morbidity (10-fold and fivefold increased risk respectively); while lymphocytopenia was associated with maternal morbidity [ 23 ]. A study from India also attributed the increased perinatal mortality directly to increased severity of maternal infection, and indirectly to increased obstetrical complications due to disrupted maternal services [ 7 ].…”
Section: Discussionmentioning
confidence: 99%